The Complementary Effect between Private Consumption and Government Spending: Effect on the Economy - Kida Nakije (Emerging Science Journal, 2021)
This paper analyzes the relationship between final consumption and government spending, using the correlation and linear regression model. The objective of the research is whether government expenditures are complementary, substitute, or not related to private consumption to give positive effects on the economy. Methodology, quantitative secondary data were obtained from the World Bank, for five countries and processed with SPSS, 21. The empirical analysis was verified through, Bivariate and Partial correlation and normality test. The Result, first, shows that government spending complements and replaces final consumption. Second, it is also confirmed that even when interacting with other variables, the complementary effect of final consumption is not eliminated despite the shocks coming from government spending. Third, by adding other variables to the model, the issue of complementarity and substitutability of the two main variables is not lost. As a result, findings, confirm that private consumption (InCt) and government spending (InGt), Gross Savings (GS), and per capita income (GDPpc), are in statistically significant and positive relationships with each other. The novelty of the paper is, government expenditures cause an increase in private consumption is to high value, showing the complementary effect of government expenditures on private consumption. Based on health expenditures, education, public order, internet provided by the state have increased the demand of families for these services, causing an increase in the share of services provided by the private sector.JEL Classification: E21; H5; E2; R0. Doi: 10.28991/esj-2021-01292 Full Text: PDF